Effect of balcony forms difference on indoor thermal environment and energy saving performance of multiple-dwelling house - Yuan, Xin; Ryu, Yuji; Sekartaji, Dian (Frontiers in Energy Research, 2022)
By optimizing the design of the building envelope, it is possible to create a more comfortable and energy-efficient indoor environment for the occupants. However, due to environmental issues in high-density cities, open balconies might affect the health of occupants. The current research focuses on the effect of a single balcony form in different climates, which could be detrimental to the diversity of balcony designs. Therefore, it is necessary to re-examine the rationality of traditional Japanese open balconies in terms of building envelope design and living environment to optimize the indoor thermal environment and reduce the energy consumption of dwellings. Focusing on Kitakyushu, Japan, which is in a warm climate, this paper conducts a comprehensive comparative study of the effects of building envelope design for residential buildings, including balcony form, thermal insulation performance, room orientation, and the window-to-wall ratio of balcony facades. The results of the study indicate that (1) the closed balcony design is strongly applicable to houses in warm climate regions in winter; (2) closed balconies facing south have a more positive impact on the indoor thermal environment, and energy-saving performance than open balconies; (3) even closed balconies without insulation could achieve higher thermal environment gains than open balconies with insulation. Designing a special type of closed balcony for residences in winter is more energy-efficient than insulation. This study proposes architectural envelope designs that are adapted to specific environmental and climatic conditions. It contributes to providing residential designers with a measure of how to provide a comfortable residential thermal environment and energy efficiency for occupants through architectural envelope design.